Epidemiology, Etiology, and Prevention of Late IOL-Capsular Bag Complex Dislocation: Review of the Literature - Ascaso, Francisco J. (J Ophthalmol, 2015)
Posterior chamber intraocular lens (PC-IOL) subluxation is uncommon but represents one of the most serious complications following phacoemulsification. Late spontaneous IOL-capsular bag complex dislocation is defined as occurring three months or later following cataract surgery. Unlike early IOL dislocation, late spontaneous IOL dislocation is due to a progressive zonular dehiscence and contraction of the capsular bag many years what seemed to be uneventful surgery. In recent years, late in-the-bag IOL subluxation or dislocation has been reported with increasing frequency, having a cumulative risk of IOL dislocation following cataract extraction of 0.1% after 10 years and 1.7% after 25 years. A predisposition to zonular insufficiency and capsular contraction is identified in 90% of reviewed cases. Multiple conditions likely play a role in contributing to this zonular weakness and capsular contraction. Pseudoexfoliation is the most common risk factor, accounting for more than 50% of cases. Other associated conditions predisposing to zonular dehiscence are aging, high myopia, uveitis, trauma, previous vitreoretinal surgery, retinitis pigmentosa, diabetes mellitus, atopic dermatitis, previous acute angle-closure glaucoma attack, and connective tissue disorders. The recognition of these predisposing factors suggests a modified approach in cases at risk. We review certain measures to prevent IOL-bag complex luxation that have been proposed.